ANALISIS KINERJA KANTOR KECAMATAN KARANGSAMBUNG KABUPATEN KEBUMEN - Siti Amanah; Endang Larasati; Sundarso Sundarso (Journal of Public Policy and Management Review, 2015)
Performance is a result of person or organization that obtained as a whole within a certain time period organizational performance is the organization's ability to perform the task well to achieve the goals and vision that has been determined. Sub-district position is the county area or city as a regional technical implementation that has a particular work area and led by Camat . District of Karangsambung’s vision namely the creation of excellent service based on professionalism. The purpose of this study is to know the performance of Karangsambung District Office and to know factors that support and hinder performance Karangsambung District Office. Assessment of the performance at the District Office Karangsambung is seen from the five dimensions of productivity, quality of service, responsiveness, responsibility, and accountability. While the factors that support and hinder the performance of the District Office Karangsambung are seen from human resources and existing infrastructure. This study uses descriptive qualitative. Based on the existing barriers in performance, the author provide recommendations: 1) Increasing the capacity of human resources in the district ad a Karangsambung. 2) Instilling discipline and responsibility to the employees. 3) Giving motivation to the employees. 4) Providing facilities and infrastructure in order to increase the service to the public. 5) Communication with the public needs to be more intensive through formal and informal media so people know that there is information 6) Managing Karangsambung’s website as a transparency of information means.